The humanities in the 21st century. Report on the round table - Maragda Royo Meya; Marisa Casillas Allés; Miquel Bou Planas (Digithum, 2004)
The 1st Conference on Humanities Professions in the Knowledge Society, organised by the UOC’s Humanities and Philology department, took place on October 1st 2003 and was made up of three round tables: “The Humanities in the 21st century”, “Professional openings and expectations for graduates” and “The humanities seen from a professional and employment perspective”. This document, produced by students of the UOC’s Humanities degree, compiles in a report the aspects that the authors believe to be most important from the contributions made at the first of the round tables (Joan Campàs, professor of Humanities at the UOC, Josep Maria Terricabras, professor of Philosophy at the University of Girona, and Artur Serra, researcher at the Polytechnic University of Catalonia) and the subsequent discussion.La I Jornada sobre las Profesiones de las Humanidades en la Sociedad del Conocimiento, organizada por los Estudios de Humanidades y Filología de la UOC, que se celebró el pasado 1 de octubre de 2003, constó de tres mesas redondas: "Las Humanidades en el siglo XXI", "Expectativas y salidas profesionales de los licenciados y licenciadas" y "Las Humanidades vistas desde el mundo laboral y profesional". En este documento, elaborado por estudiantes de la propia titulación de Humanidades de la UOC, se reúnen en forma de crónica los aspectos que los autores han considerado más relevantes de las aportaciones de los ponentes de la primera de las mesas redondas (Joan Campàs, profesor de Humanidades de la UOC, Josep Maria Terricabras, profesor de Filosofía de la Universidad de Gerona, y Artur Serra, investigador de la Universidad Politécnica de Cataluña) y del posterior coloquio. La I Jornada sobre les Professions de les Humanitats en la Societat del Coneixement, organitzada pels Estudis d'Humanitats i Filologia de la UOC, que va tenir lloc el passat 1 d’octubre de 2003, va constar de tres taules rodones: "Les Humanitats en el segle XXI", “Expectatives i sortides professionals dels llicenciats i llicenciades” i "Les Humanitats vistes des del món laboral i professional". En aquest document, elaborat per estudiants de la titulació d’Humanitats de la UOC, es recullen en forma de crònica els aspectes que els autors han considerat més rellevants de les aportacions dels ponents de la primera de les taules rodones (Joan Campàs, professor d'Humanitats de la UOC, Josep Maria Terricabras, professor de Filosofia de la Universitat de Girona, i Artur Serra, investigador de la Universitat Politècnica de Catalunya) i del posterior col·loqui.